2020
DOI: 10.1111/jcal.12442
|View full text |Cite
|
Sign up to set email alerts
|

Dual computer displays reduce extraneous cognitive load

Abstract: Dual display desktop computers are becoming more prevalent in the home, workplace, and schools, yet there has been little research into how learning and productivity are impacted by having a second display. One useful method in exploring this question is to measure cognitive load during an intensive learning event. This study compared perceived cognitive load among participants in a military training program using one or two computer displays. Participants using dual monitors reported lower unnecessary cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…The results of these studies indicate that ECL students are in the high category (Juanengsih, Rahmat, Wulan & Rahman, 2018a) Based on the results of these measurements, it is recommended that there must be an attempt to enhance the process of learning an effort to improve the learning process in cell biology lectures. The most recent ECL research was conducted by Miller, Stenmark & Ittersum (2020), who found that ECL can be reduced by several information displays.…”
Section: Related Studiesmentioning
confidence: 99%
“…The results of these studies indicate that ECL students are in the high category (Juanengsih, Rahmat, Wulan & Rahman, 2018a) Based on the results of these measurements, it is recommended that there must be an attempt to enhance the process of learning an effort to improve the learning process in cell biology lectures. The most recent ECL research was conducted by Miller, Stenmark & Ittersum (2020), who found that ECL can be reduced by several information displays.…”
Section: Related Studiesmentioning
confidence: 99%
“…However, learning in virtual environments can introduce additional cognitive load (e.g., Makransky, Terkildsen, & Mayer, 2019). Although previously usually considered mainly as a means to support research on learning (Paas, Tuovinen, Tabbers, & van Gerven, 2003), finding ways of lowering cognitive load in the design of tasks has become a research area of its own (e.g., Miller, Stenmark, & Ittersum, 2020). As there is a plethora of cognitive load measurement methods, each with their own advantages and disadvantages, it can be overwhelming for researchers to choose an appropriate method of cognitive load measurement.…”
mentioning
confidence: 99%